Carbon nanotube dispersion, method for preparing same, electrode slurry composition comprising same, electrode comprising same, and secondary battery comprising same

By adding sulfur elements to the carbon nanotube dispersion, the problem of degradation of dispersion due to excessive binding force between the dispersants is solved, and the carbon nanotube dispersion with low viscosity and high dispersion is achieved, which improves the performance of the electrode and the battery.

CN119836398APending Publication Date: 2025-04-15BETTERIAL CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202380063764.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-05
Filing Date
2023-08-14
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

In the prior art, the dispersion of the carbon nanotube dispersion liquid decreases due to the excessive binding force between the first dispersant and the second dispersant, which affects the conductivity of the electrode and the capacity of the battery.

Method used

By adding sulfur elements to the carbon nanotube dispersion liquid, hydrogen bond formation between the first dispersant and the second dispersant is inhibited, and aggregation of the dispersant is reduced, thereby improving the dispersibility of the carbon nanotubes.

Benefits of technology

The low viscosity and high dispersion of the carbon nanotube dispersion liquid are achieved, and the conductivity of the electrode and the capacity of the secondary battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005296952310000061
    Figure BDA0005296952310000061
  • Figure BDA0005296952310000071
    Figure BDA0005296952310000071
  • Figure BDA0005296952310000072
    Figure BDA0005296952310000072
Patent Text Reader

Abstract

The present invention relates to a carbon nanotube dispersion liquid, a method for preparing the same, an electrode slurry composition comprising the same, an electrode comprising the same, and a secondary battery comprising the same, the carbon nanotube dispersion liquid comprising: carbon nanotubes; a first dispersant having an amide group; a second dispersant having one or more functional groups selected from the group consisting of a hydroxyl group and a carboxyl group; and a sulfur element.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This article claims the priority of Patent Application No. 10-2022-0112212 filed in the Korean Intellectual Property Office on September 5, 2022, the contents of which are incorporated herein.

[0002] The present invention relates to a carbon nanotube dispersion, a preparation method thereof, an electrode slurry composition containing the same, an electrode containing the same, and a secondary battery containing the same. Background Art

[0003] A secondary battery is a battery that can be reused through a discharge process that converts chemical energy into electrical energy and a reverse charging process. A secondary battery consists of a positive electrode, a negative electrode, an electrolyte, and a separator. The positive electrode and the negative electrode generally include: an electrode current collector; and an electrode active material layer formed on the electrode current collector. The electrode active material layer is formed by applying an electrode slurry composition including an electrode active material, a conductive material, a binder, etc. to the electrode current collector, and rolling it after drying.

[0004] Conductive materials are used to improve the conductivity of electrode active materials. In the past, point-shaped conductive materials such as carbon black were mainly used. However, since point-shaped conductive materials are not very effective in improving conductivity, they must be used in excess to achieve a sufficient effect, which leads to a decrease in the content of electrode active materials, thereby causing a problem of reduced battery capacity.

[0005] In order to improve this problem, attempts are being made to use highly conductive carbon nanotubes (CNT) as conductive materials. Since carbon nanotubes can achieve high conductivity even when used in small amounts, the use of carbon nanotubes can significantly reduce the content of conductive materials compared to the use of carbon black, thereby having the advantage of increasing capacitance.

[0006] In order to use carbon nanotubes as negative electrode conductive materials, from a process point of view, it is necessary to prepare a low-viscosity aqueous dispersion.

[0007] Polyvinylpyrrolidone (PVP) is a dispersant having an amide group and is used as a polymer surfactant in various dispersion systems as a dispersant, emulsifier, thickener, etc. It is known to be effective for dispersing carbon nanotubes (Patent Document 1).

[0008] In addition, polyacrylic acid and tannic acid belong to the polyacids containing a carboxyl group, and are also known to be effective for dispersing carbon nanotubes.

[0009] Based on the above, it can be inferred that a better CNT dispersion effect can be obtained when polyvinyl pyrrolidone and polyacid are mixed. However, in fact, when these substances are mixed, there is usually an overly strong binding force between the two substances, forming insoluble matter or agglomerates, which leads to a problem that the dispersibility of the dispersion is reduced.

[0010] Prior art literature

[0011] Patent Literature

[0012] Patent Document 1: KR No. 10-2011-0118460

[0013] Non-patent literature

[0014] Non-patent literature 1: Journal of Toxicological Research (Toxicol. Res., 2015, 4, 160-168) Summary of the invention

[0015] Technical issues

[0016] The present invention relates to a carbon nanotube dispersion liquid with improved carbon nanotube dispersibility, a preparation method thereof, an electrode slurry composition containing the same, an electrode containing the same and a secondary battery containing the same.

[0017] Solutions to the problem

[0018] An embodiment of the present invention provides a carbon nanotube dispersion liquid, which comprises:

[0019] Carbon nanotubes;

[0020] a first dispersant having an amide group;

[0021] A second dispersant having one or more functional groups selected from the group consisting of a hydroxyl group and a carboxyl group; and

[0022] Sulfur element.

[0023] Furthermore, another embodiment of the present invention provides a method for preparing the carbon nanotube dispersion, which comprises the step of mixing carbon nanotubes, a first dispersant having an amide group, and a second dispersant having one or more functional groups selected from the group consisting of a hydroxyl group and a carboxyl group.

[0024] Furthermore, another embodiment of the present invention provides an electrode slurry composition, which includes the carbon nanotube dispersion, a silicon-based electrode active material, and a binder.

[0025] Furthermore, another embodiment of the present invention provides an electrode including an electrode active material layer formed from the electrode slurry composition.

[0026] Furthermore, another embodiment of the present invention provides a secondary battery including the above-mentioned electrode.

[0027] Effects of the Invention

[0028] The carbon nanotube dispersion liquid according to the embodiment of the present invention has a significantly low viscosity and has the effect of improving the dispersibility of the carbon nanotubes in the dispersion liquid.

[0029] The carbon nanotube dispersion liquid according to the embodiment of the present invention has the effect of being excellent in coating properties and processability when used for producing an electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is the result of Experimental Example 1.

[0031] Figures 2 to 4 This is a result of confirming whether the first dispersant used in Examples and Comparative Examples contains sulfur. DETAILED DESCRIPTION

[0032] Best Mode for Carrying Out the Invention

[0033] The present invention is described in detail below.

[0034] The carbon nanotube dispersion liquid according to the embodiment of the present invention refers to a dispersion liquid containing carbon nanotubes. Specifically, it means that the carbon nanotubes are dispersed in the dispersion liquid without agglomerating with each other.

[0035] An embodiment of the present invention provides a carbon nanotube dispersion liquid, which includes: carbon nanotubes; a first dispersant having an amide group; a second dispersant having one or more functional groups selected from the group consisting of a hydroxyl group and a carboxyl group; and sulfur.

[0036] It is known that a first dispersant having an amide group is effective for dispersing carbon nanotubes (Patent Document 1), and a second dispersant having one or more functional groups selected from the group consisting of a hydroxyl group and a carboxyl group is known to reduce the viscosity of the dispersion due to the influence of the functional group (Non-Patent Document 1).

[0037] In addition, the oxygen of the amide group contained in the first dispersant and the functional group (hydroxyl or carboxyl group) of the second dispersant form hydrogen bonds with each other, which has the effect of helping to reduce the viscosity of the dispersion. However, there is a problem that the above hydrogen bonds are too strong, forming insoluble matter or agglomerates (complex). In this case, there are many restrictions on the selection of dispersants, such as the need to adjust the content of the first dispersant and the second dispersant, or the need to use specific types of the first dispersant and / or the second dispersant.

[0038] The inventors have found that when the dispersion contains sulfur, the phenomenon of mutual aggregation of the first dispersant and the second dispersant is improved, thereby completing the present invention. In this case, even if carbon nanotubes with a large specific surface area are contained, the dispersion has the effect of maintaining a low viscosity. The improvement of the aggregation phenomenon can be confirmed by preparing a carbon nanotube dispersion containing the above substances, leaving it for a predetermined time, and then visually observing whether aggregation occurs.

[0039] The carbon nanotube dispersion of the embodiment of the present invention has the characteristics of containing carbon nanotubes with excellent conductivity and improving the dispersibility of the carbon nanotubes, thereby minimizing the phenomenon of carbon nanotubes agglomerating with each other. The above characteristics can be confirmed from the significantly low viscosity of the dispersion.

[0040] The carbon nanotube dispersion of an embodiment of the present invention is characterized in that it contains sulfur. The sulfur element can be present in the dispersion in the form of a compound, an element, or an ion. For example, the sulfur element can be derived from a sulfur-containing compound, which will be described later. The presence and content of the sulfur element can be confirmed by elemental analysis.

[0041] In an embodiment of the present invention, based on the solid content, the sulfur content in the carbon nanotube dispersion can be 0.01wt% to 10wt%, 0.05wt% to 8wt%, or 0.1wt% to 5wt%. The above sulfur content can be achieved by adjusting the content of the sulfur-containing compound. The sulfur content can be measured and calculated using an elemental analyzer (EA), and the specific method will be described later.

[0042] In an embodiment of the present invention, the content of sulfur element can be 0.01% to 20%, 0.1% to 10%, or 1% to 5% based on the total content of oxygen (O) and nitrogen (N) elements in the solid component. When the above numerical range is met, by adjusting the ratio of the content of oxygen and nitrogen elements participating in hydrogen bonding to the content of sulfur element, the dispersant can be prevented from agglomerating with each other and the dispersibility of carbon nanotubes can be improved. The content of the above elements can be measured and calculated using an elemental analyzer (EA), and the specific method will be described later.

[0043] In an embodiment of the present invention, part or all of the first dispersant may be substituted with sulfur. When part of the first dispersant is substituted with sulfur, the remaining first dispersant may not be substituted with sulfur. For example, a first dispersant substituted with sulfur and a first dispersant not substituted with sulfur may be used together.

[0044] In an embodiment of the present invention, the ratio of the first dispersant substituted by sulfur in the first dispersant may be 10 mol % to 100 mol %, 20 mol % to 80 mol % or 40 mol % to 60 mol %.

[0045] In an embodiment of the present invention, the first dispersant may include a 1110 cm -1 Up to 1050cm -1 The first peak, 1140cm -1 Up to 1180cm -1 The second peak at 1180 cm -1 Up to 1220cm -1 The first to third peaks indicate the presence of an S=0 bond in the dispersant. When the peaks appear, it can be confirmed that the first dispersant is substituted with sulfur.

[0046] In an embodiment of the present invention, the first dispersant has an amide group, and thus can form a hydrogen bond with a hydroxyl group or a carboxyl group of a second dispersant described later.

[0047] In an embodiment of the present invention, the first dispersant may be polyvinylpyrrolidone, polyester amide, polycarboxylicamide, polyamido amine, thioamido amine, water soluble nylon or a combination thereof. The first dispersant has an amide group, thereby further improving the viscosity improvement effect and inhibiting the viscosity change over time.

[0048] In an embodiment of the present invention, the weight average molecular weight of the first dispersant may be 1000 g / mol to 100000 g / mol, preferably 2000 g / mol to 80000 g / mol, more preferably 2000 g / mol to 30000 g / mol, and further preferably 2000 g / mol to 15000 g / mol. If the weight average molecular weight of the first dispersant is less than 1000 g / mol, the dispersion performance of the carbon nanotubes may decrease, and the problem of dissolution of the first dispersant may occur when manufacturing the electrode. If it exceeds 100000 g / mol, the viscosity of the carbon nanotube dispersion increases, which may lead to reduced coating and process properties. Therefore, it is preferably adjusted to the above range.

[0049] In an embodiment of the present invention, the second dispersant has a hydroxyl group or a carboxyl group, and thus can form a hydrogen bond with the amide group of the first dispersant.

[0050] In an embodiment of the present invention, the second dispersant may contain an aromatic ring. In this case, the second dispersant has a complex structure, thereby effectively reducing the viscosity of the dispersion.

[0051] In an embodiment of the present invention, the second dispersant may contain two or more aromatic rings. For example, the second dispersant may be one or more selected from the group consisting of baicalin, luteolin, taxifolin, myricetin, quercetin, rutin, catechin, epigallocatechin gallate, butein, cortin and tannic acid, preferably tannic acid, quercetin, epigallocatechin gallate or a combination thereof.

[0052] In an embodiment of the present invention, the second dispersant may be a phenol compound. In the phenol compound, one or more of the aromatic rings may include one or more structures selected from the group consisting of a phenol structure, a catechol structure, a gallol structure and a naphthol structure. The phenol structure is a structure in which one hydroxyl group is combined with a benzene ring, the catechol structure is a structure in which two hydroxyl groups are combined with a benzene ring, the gallol structure is a structure in which three hydroxyl groups are combined with a benzene ring, and the naphthol structure is a structure in which one hydroxyl group is combined with a naphthalene.

[0053] In an embodiment of the present invention, the second dispersant may be a polyacrylic acid compound. The polyacrylic acid compound refers to an acrylic acid compound containing two or more acidic hydrogen atoms.

[0054] In an embodiment of the present invention, the polyacrylic acid compound may be polyacrylic acid {Poly (acrylic acid): PAA} or a polyacrylic acid derivative. The polyacrylic acid derivative may be polyacrylic acid-maleic acid copolymer (PAAMA).

[0055] In an embodiment of the present invention, the second dispersant may include a compound containing an aromatic ring, a polyacrylic acid compound, or a combination thereof. The compound containing an aromatic ring and the polyacrylic acid compound are as described above.

[0056] In an embodiment of the present invention, the weight ratio of the first dispersant to the second dispersant may be 1:10 to 10:1, 1:5 to 5:1 or 1:1 to 1:5. When the above range is met, the dispersion effect of the carbon nanotubes is improved, thereby maintaining a low dispersion viscosity.

[0057] In an embodiment of the present invention, based on the total weight of the dispersion, the content of the first dispersant may be 0.01 wt % to 10 wt %, 0.01 wt % to 5 wt % or 0.1 wt % to 3 wt %.

[0058] In an embodiment of the present invention, based on the total weight of the dispersion, the content of the second dispersant may be 0.01 wt % to 10 wt %, 0.01 wt % to 5 wt % or 0.1 wt % to 3 wt %.

[0059] In an embodiment of the present invention, the carbon nanotube is intended to improve the conductivity of the electrode, has a cylindrical graphite sheet with a nanometer diameter, and has an sp2 bonding structure. In this case, according to the angle and structure of the winding of the graphite sheet, the characteristics of a conductor or a semiconductor are exhibited. Carbon nanotubes can be divided into single-walled carbon nanotubes (SWCNT, single-walled carbon nanotube), double-walled carbon nanotubes (DWCNT, doublewalled carbon nanotube) and multi-walled carbon nanotubes (MWCNT, multi-walled carbon nanotube) according to the number of bonds forming the wall, and these carbon nanotubes can be appropriately selected according to the purpose of the dispersion. In addition, the carbon nanotube can have a secondary shape formed by agglomeration or arrangement of multiple carbon nanotubes, for example, it can be a bundle (bundle) or rope (rope) of a bundle type (bundle type) carbon nanotube in which multiple carbon nanotubes are arranged side by side or in a prescribed direction, or it can be a tangled type (entangled type) carbon nanotube in which multiple carbon nanotubes are entangled with each other in a spherical or potato shape without a prescribed direction.

[0060] In an embodiment of the present invention, the carbon nanotubes may be single-walled carbon nanotubes (SWCNTs) or multi-walled carbon nanotubes (MWCNTs).

[0061] In an embodiment of the present invention, the specific surface area (BET) of the carbon nanotubes may be 10 m 2 / g to 5000m 2 / g, preferably 30m 2 / g to 3000m 2 / g, more preferably 50m 2 / g to 2000m 2 When the above numerical range is satisfied, the conductivity improvement effect is excellent. The specific surface area (BET) of the carbon nanotubes may vary depending on the type of carbon nanotubes.

[0062] In an embodiment of the present invention, the specific surface area (BET) of the single-walled carbon nanotubes may be 800 m2 / g to 5000m 2 / g, preferably 800m 2 / g to 3000m 2 / g, more preferably 900m 2 / g to 2000m 2 When the above numerical range is satisfied, the conductivity-enhancing effect is excellent.

[0063] In an embodiment of the present invention, the specific surface area (BET) of the multi-walled carbon nanotubes may be 10 m 2 / g to 1200m 2 / g, preferably 30m 2 / g to 1000m 2 / g, more preferably 50m 2 / g to 800m 2 When the above numerical range is satisfied, the conductivity-enhancing effect is excellent.

[0064] In an embodiment of the present invention, the content of the carbon nanotubes may be 0.01wt% to 10wt%, preferably 0.1wt% to 8wt%, based on the total weight of the carbon nanotube dispersion. The content of the carbon nanotubes may be appropriately adjusted according to the specific surface area of ​​the carbon nanotubes. For example, when using a carbon nanotube dispersion having a specific surface area of ​​800m 2 When the carbon nanotube content is more than 100 wt % / g, the content of the carbon nanotubes can be about 0.01 wt % to 5 wt %, preferably about 0.01 wt % to 3 wt %, and more preferably about 0.01 wt % to 2 wt % based on the total weight of the carbon nanotube dispersion. When the specific surface area and content of the carbon nanotubes exceed the above ranges, problems such as increased process costs due to decreased loading during electrode manufacturing, decreased adhesion due to binder migration during electrode drying, or increased viscosity of the carbon nanotube dispersion may occur.

[0065] In an embodiment of the present invention, the carbon nanotube may include more than two carbon nanotube monomers. The carbon nanotube monomer has a cylindrical graphite sheet with a nanometer-scale diameter and has an sp2 bonding structure.

[0066] In an embodiment of the present invention, the diameter of the carbon nanotube monomer may be 1 nm to 200 nm, 1 nm to 150 nm, or 1 nm to 100 nm. Within the above numerical range, the dispersibility of the carbon nanotube can be improved, and when applied to an electrode, the resistance can be prevented from increasing.

[0067] In an embodiment of the present invention, the length of the carbon nanotube monomer may be 0.1 μm to 200 μm, 0.1 μm to 150 μm, or 0.5 μm to 100 μm. Within the above numerical range, the dispersibility of the carbon nanotube can be improved, and when applied to an electrode, the resistance can be prevented from increasing.

[0068] In an embodiment of the present invention, the aspect ratio (length / diameter) of the carbon nanotubes may be 5 to 50000 or 10 to 15000. Within the above numerical range, the dispersibility of the carbon nanotubes may be improved, and when applied to an electrode, an increase in resistance may be prevented.

[0069] In an embodiment of the present invention, the average particle size (D50) of the carbon nanotubes may be 0.1 μm to 20 μm, 0.5 μm to 1 μm, 1 μm to 5 μm, or 2 μm to 4 μm. The average particle size (D50) refers to the particle size corresponding to 50% of the cumulative number of particles in the particle size distribution curve of the carbon nanotubes. For example, the average particle size (D50) may be measured using a laser diffraction method. Within the above range, the carbon nanotubes do not agglomerate with each other and the dispersibility may be improved.

[0070] In an embodiment of the present invention, the carbon nanotube dispersion is heated at 25°C for 15 seconds. -1 The viscosity at a shear rate of 4000 cPs or less, 3000 cPs or less, 1000 cPs or less, or 600 cPs or less. Considering the purpose of the present invention, the lower the viscosity, the better, so the lower limit is not particularly limited, and can be 10 cPs or more, 30 cPs or more, or 50 cPs or more. When the above viscosity range is met, the carbon nanotubes of the carbon nanotube dispersion do not agglomerate with each other, and have a process improvement effect when used for electrode manufacturing.

[0071] The viscosity of the carbon nanotube dispersion can be measured by a method commonly used in the art. For example, a Brookfield DVNext CP Rheometer can be used at a measurement temperature of 25°C and a flow rate of 15 seconds. -1 For more accurate measurement, the prepared carbon nanotube dispersion can be stored at 25°C for 1 week before measurement.

[0072] In an embodiment of the present invention, the value of the carbon nanotube dispersion represented by the following formula 1 may be 2 to 10, 2 to 6.5, or 3 to 6. The value represented by the following formula 1 is the shear fluidization index of the dispersion, which refers to the ratio of the viscosity measured at different shear rates. When the above range is met, the fluidity is prevented from decreasing due to excessive viscosity in a static state, so that the electrode can be uniformly mixed during manufacture. In addition, the storage stability can be improved by preventing the deposition of carbon nanotube particles.

[0073] Formula 1

[0074] Shear Thinning Index (STI) = V low / V high

[0075] In the above formula 1,

[0076] V low At 25℃ and 15sec -1 The viscosity of the dispersion measured at a shear rate of

[0077] V high At 25℃ and 150sec -1 The viscosity of the dispersion is measured at a shear rate of .

[0078] In an embodiment of the present invention, the value of the above-mentioned carbon nanotube dispersion calculated by the following formula 2 can be 1 to 5, 1 to 3 or 1.1 to 2. The value calculated by the following formula 2 represents the relationship between the shear fluidization index (STI) characteristics of the above-mentioned dispersion and the average particle size of the carbon nanotubes contained in the dispersion. Generally, if the carbon nanotube particle size (D50) is too small, there is a tendency for the shear fluidization index (STI) of the dispersion to increase with the mutual agglomeration of the carbon nanotubes. In addition, if the carbon nanotube particle size (D50) is too large, there is a tendency for the carbon nanotubes to form a network structure due to insufficient dispersion of the carbon nanotubes, so that the overall viscosity and shear fluidization index (STI) of the dispersion increase.

[0079] However, by adjusting the value calculated by the following formula 2 to the above numerical range, the carbon nanotube dispersion according to one embodiment of the present invention has the effect of improving the temporal stability of the overall viscosity of the dispersion even if the particle size of the carbon nanotubes is small.

[0080] Formula 2

[0081]

[0082] In the above formula 2,

[0083] STI is the shear thinning index (STI) of the dispersion.

[0084] D50 is the average particle size (D50) of the carbon nanotubes.

[0085] In an embodiment of the present invention, the carbon nanotube dispersion may contain an alkali metal element. Since the carbon nanotube dispersion of the present invention contains the alkali metal element, the dispersibility of the substance contained in the dispersion can be improved. Specifically, the first dispersant and the second dispersant contained in the dispersion can form a complex with each other, but the solubility of the complex in solvents such as water is low, thereby increasing the viscosity of the dispersion. However, the alkali metal contained in the carbon nanotube dispersion of the present invention can solve the above problem by decomposing the complex.

[0086] In the embodiment of the present invention, the form of the alkali metal is not particularly limited, but the alkali metal may be present in the form of an alkali metal salt containing the alkali metal.

[0087] In an embodiment of the present invention, the content of the alkali metal element based on the entire carbon nanotube dispersion may be 1 ppm to 300 ppm, 5 ppm to 200 ppm, or 5 ppm to 150 ppm.

[0088] In an embodiment of the present invention, the carbon nanotube dispersion may include one or more alkali metal salts selected from the group consisting of KOH, NaOH, LiOH, K2CO3, Na2CO3 and LiCO3.

[0089] In an embodiment of the present invention, when the first dispersant is a polyvinyl pyrrolidone resin, the molar ratio of the alkali metal salt can be 60 mol or less, 30 mol or less, or 25 mol or less based on 100 mol of the vinyl pyrrolidone monomer. The lower limit of the content is not particularly limited, but can be 0.1 mol or more, 1 mol or more, or 2 mol or more. When the above range is met, the viscosity of the carbon nanotube dispersion can be adjusted at 25°C and 15 sec. -1 The shear rate was adjusted to be below 1300 cPs.

[0090] The molar ratio of the alkali metal salt can be calculated using the molecular weights of the alkali metal salt and the vinyl pyrrolidone monomer and the weight percentages of the alkali metal salt and the polyvinyl pyrrolidone. Specifically, it can be calculated using the following formula 3.

[0091] Formula 3

[0092] Molar ratio of alkali metal salt = {(weight percentage of alkali metal salt) / (molecular weight of alkali metal salt)} / {(weight percentage of polyvinyl pyrrolidone) / (molecular weight of vinyl pyrrolidone monomer)}*100

[0093] For example, when the contents of polyvinyl pyrrolidone and alkali metal salt (LiOH) are 0.6 wt% and 0.01 wt% respectively based on the total weight of the dispersion, the molecular weight of the alkali metal salt (LiOH) is 24 g / mol, and the molecular weight of the vinyl pyrrolidone monomer is 111.14 g / mol, the molar ratio of the alkali metal salt is calculated to be 7.7 mol [7.7 = {(0.01) / (24)} / {(0.6) / (111.14)}*100 based on 100 mol of the vinyl pyrrolidone monomer]

[0094] The vinyl pyrrolidone monomer is a monomer formed by connecting a 5-membered lactam and a vinyl group, and is a unit constituting the polyvinyl pyrrolidone resin. Specifically, it can be a monomer represented by Chemical Formula 2 in the polyvinyl pyrrolidone represented by Chemical Formula 1 below.

[0095] Chemical formula 1

[0096]

[0097] Chemical formula 2

[0098]

[0099] In an embodiment of the present invention, the carbon nanotube dispersion may further include a solvent. The solvent is used to disperse the carbon nanotubes and provide the carbon nanotube dispersion to prevent the carbon nanotubes from agglomerating when the carbon nanotubes are directly mixed with an electrode active material and used as an electrode slurry composition.

[0100] In an embodiment of the present invention, the solvent may be an aqueous solvent. For example, the aqueous solvent may be water. In this case, the viscosity of the dispersion is easily adjusted, and no toxic substances are generated.

[0101] An embodiment of the present invention provides a method for preparing a carbon nanotube dispersion, which includes mixing carbon nanotubes, a first dispersant having an amide group, and a second dispersant having one or more functional groups selected from the group consisting of a hydroxyl group and a carboxyl group.

[0102] In an embodiment of the present invention, the step of mixing the carbon nanotubes, the first dispersant having an amide group, and the second dispersant having one or more functional groups selected from the group consisting of a hydroxyl group and a carboxyl group can be performed at a temperature that does not change the physical properties. For example, it can be performed below 50°C, and more specifically, it can be performed at a temperature of 5°C to 50°C.

[0103] In an embodiment of the present invention, the step of dispersing the carbon nanotubes in the dispersion liquid can be carried out by a ball mill, a bead mill, a disc mill or a basket mill, a high pressure homogenizer, etc., and more specifically, it can be carried out by a grinding method using a disc mill or a high pressure homogenizer.

[0104] When grinding using the above disc mill, the size of the beads can be appropriately determined according to the type and amount of carbon nanotubes and the type of dispersant, and specifically, the diameter of the beads can be 0.1 mm to 5 mm, more specifically, 0.5 mm to 4 mm. In addition, the bead milling process can be performed at a speed of 2000 rpm to 10000 rpm, more specifically, at a speed of 5000 rpm to 9000 rpm.

[0105] The grinding using the high pressure homogenizer is achieved by, for example, pressurizing the mixture with a plunger pump of the high pressure homogenizer and pushing it through the gap of the homogenizing valve, thereby generating cavitation, shear, impact and explosion forces when passing through the gap.

[0106] In an embodiment of the present invention, the step of dispersing the carbon nanotubes in the dispersion liquid may be performed for 10 minutes to 120 minutes, more specifically, for 20 minutes to 90 minutes, so that the carbon nanotubes can be fully dispersed.

[0107] An embodiment of the present invention provides an electrode slurry composition, which includes the carbon nanotube dispersion, an electrode active material and a binder.

[0108] In an embodiment of the present invention, the electrode active material includes a silicon-based electrode active material. The silicon-based electrode active material may include one or more of the group consisting of metallic silicon (Si), silicon oxide (SiOx, wherein 0 < x < 2), silicon carbide (SiC) and Si-Y alloy (the above Y is an element selected from the group consisting of alkali metals, alkaline earth metals, group 13 elements, group 14 elements, transition metals, rare earth elements and combinations thereof, and is not Si). The element Y may be selected from the group consisting of Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ti, Ge, P, As, Sb, Bi, S, Se, Te, Po and combinations thereof.

[0109] In an embodiment of the present invention, since the above-mentioned silicon-based electrode active material exhibits higher capacity characteristics than the carbon-based electrode active material, when the silicon-based electrode active material is further included, a more excellent capacity characteristic can be obtained. However, the volume of the silicon-based electrode active material increases during charge and discharge, so when repeated charge and discharge, the battery characteristics deteriorate rapidly, resulting in insufficient cycle characteristics, which makes it difficult to commercialize. However, when carbon nanotubes are used as conductive materials like the present invention, the application of silicon-based electrode active materials can obtain the effect of improving the cycle characteristics. Therefore, by using the electrode slurry composition of the present invention comprising the carbon nanotube dispersion of the present invention and the silicon-based electrode active material, a secondary battery with excellent capacity characteristics and cycle characteristics can be achieved.

[0110] In an embodiment of the present invention, the electrode active material may include other types of electrode active materials in addition to the silicon-based electrode active material. As the other types of electrode active materials, for example, carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon can be used; metallic compounds that can form alloys with lithium, such as Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, or Al alloys; metal oxides that can be doped or dedoped with lithium, such as SnO2, vanadium oxide, lithium vanadium oxide, etc.; or composite materials comprising metallic compounds and carbonaceous materials, such as Sn-C composites, wherein carbonaceous materials are particularly preferred.

[0111] In an embodiment of the present invention, based on the total solid content in the electrode slurry composition, the total amount of the electrode active material after the silicon-based electrode active material and other types of electrode active materials are added can be 70wt% to 99wt%, preferably 80wt% to 98wt%. When the content of the electrode active material meets the above range, excellent capacity characteristics can be achieved.

[0112] In an embodiment of the present invention, the above-mentioned binder is used to ensure the adhesion between the active materials or between the active materials and the current collector, and a general binder used in the present technical field can be used, and its type is not particularly limited. As the above-mentioned binder, polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile (polyacrylonitrile), carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber or various copolymers thereof can be cited, and one of them can be used alone or a mixture of two or more thereof can be used.

[0113] In an embodiment of the present invention, the content of the above-mentioned binder may be 5wt% or less, preferably 1wt% to 3wt% based on the total solid content in the electrode slurry composition. When the content of the binder satisfies the above range, the increase in electrode resistance can be minimized, and excellent electrode adhesion can be achieved.

[0114] In an embodiment of the present invention, the electrode slurry composition may further contain a solvent as needed to adjust the viscosity, etc. In this case, the solvent may be water, an organic solvent, or a mixture thereof. As the organic solvent, amide polar organic solvents such as dimethylformamide (DMF), diethylformamide, dimethylacetamide (DMAc), and N-methylpyrrolidone (NMP) may be cited; alcohols such as methanol, ethanol, 1-propanol, 2-propanol (isopropanol), 1-butanol (n-butanol), 2-methyl-1-propanol (isobutanol), 2-butanol (sec-butanol), 1-methyl-2-propanol (tert-butanol), pentanol, hexanol, heptanol, or octanol; ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, 1,3-propylene glycol, 1,3-butanediol, 1,5-pentanediol, or hexanes; The invention also includes the following: glycols such as glycol; polyols such as glycerol, trimethylolpropane, pentaerythritol or sorbitol; glycol ethers such as ethylene glycol monomethyl ether, diethylene glycol monomethyl ether, triethylene glycol monomethyl ether, tetraethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monoethyl ether, triethylene glycol monoethyl ether, tetraethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, triethylene glycol monobutyl ether, tetraethylene glycol monobutyl ether; ketones such as acetone, methyl ethyl ketone, methyl propyl ketone or cyclopentanone; esters such as ethyl acetate, γ-butyrolactone, ε-propiolactone, etc., and one of them or a mixture of two or more thereof can be used, but is not limited to this.

[0115] In an embodiment of the present invention, the electrode slurry composition may further include additives such as a viscosity modifier and a filler as needed.

[0116] An embodiment of the present invention provides an electrode comprising an electrode active material layer formed by the electrode slurry composition. Specifically, the electrode can be manufactured by applying the electrode slurry composition of the present invention and drying to form an electrode active material layer. More specifically, the electrode active material layer can be formed by a method in which the electrode slurry composition is applied to an electrode current collector and then dried, or by a method in which the electrode slurry composition is applied to another support and then peeled off from the support and the obtained film is stacked on the electrode current collector. As needed, the electrode active material layer can be formed by the above method, and then a calendering process is further performed. In this case, drying and calendering can be performed under appropriate conditions considering the performance of the electrode to be manufactured in the end, and there is no particular restriction.

[0117] In an embodiment of the present invention, the electrode current collector may be made of any material that is conductive and does not cause chemical changes in the battery, and there is no particular limitation. For example, copper, stainless steel, aluminum, nickel, titanium, alloys thereof, materials surface-treated with carbon, nickel, titanium, silver, etc., or calcined carbon may be used.

[0118] In an embodiment of the present invention, the electrode current collector may generally have a thickness of 3 μm to 500 μm, and fine concave and convex portions may be formed on the surface of the current collector to enhance the binding force of the electrode active material. Furthermore, the electrode current collector may be used in various forms, such as a film, a sheet, a foil, a net, a porous body, a foam body, a non-woven fabric body, etc.

[0119] In an embodiment of the present invention, the electrode may be a negative electrode.

[0120] An embodiment of the present invention provides a secondary battery including the above-mentioned electrode.

[0121] An embodiment of the present invention provides a secondary battery including a positive electrode, a negative electrode, and a separator and an electrolyte disposed between the positive electrode and the negative electrode, wherein at least one of the positive electrode and the negative electrode is the electrode.

[0122] In an embodiment of the present invention, the secondary battery may be a lithium secondary battery.

[0123] In an embodiment of the present invention, the above-mentioned diaphragm is used to separate the negative electrode and the positive electrode and provide a mobile channel for lithium ions, as long as it is usually used as a diaphragm in a secondary battery, it can be used without particular restrictions. Specifically, as the above-mentioned diaphragm, a porous polymer film can be used, for example, a porous polymer film made of polyolefin polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers, ethylene / methacrylate copolymers, or a stacked structure of more than two layers thereof. In addition, conventional porous non-woven fabrics can also be used, such as non-woven fabrics made of high melting point glass fibers, polyethylene terephthalate fibers, etc. In addition, a coated diaphragm containing a ceramic component or a polymer substance can also be used to ensure heat resistance or mechanical strength, and can be selectively used in a single-layer or multilayer structure.

[0124] In an embodiment of the present invention, the electrolyte may include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, molten inorganic electrolytes, etc., which can be used to manufacture secondary batteries, but are not limited thereto.

[0125] Modes for carrying out the invention

[0126] The present invention will be described in more detail below by way of examples.

[0127] <Preparation of Carbon Nanotubes>

[0128] The following carbon nanotubes were prepared.

[0129] -CNT-1 (single-walled carbon nanotube, produced by OCSiAl, product name: 01RW03, specific surface area > 800m2 / g, average diameter of monomer: 2nm)

[0130] -CNT-2 (multi-walled carbon nanotubes, prepared by JEIO, product name: 6A, specific surface area 643m 2 / g, average diameter of monomer: 9~10nm)

[0131] -CNT-3 (multi-walled carbon nanotubes, produced by LG CHEM, product name: BT1003M, specific surface area 186m 2 / g, average diameter of monomer: 13nm)

[0132] <Preparation of the first dispersant>

[0133] Inject argon (Ar) into the reactor to stabilize the atmosphere. Dissolve the monomers N-vinylpyrrolidone (N-vinylpyrrolidone) and potassium sulfite (Potassium sulfite) in water to prepare a mixed solution. Stir the mixed solution in an Ar atmosphere at 40°C for 24 hours, and then slowly cool it to room temperature. Evaporate a specified amount of water to form a concentrated state. Use acetone (Acetone) through precipitation, filtration, and drying processes to obtain PVP-1 containing sulfur element (S).

[0134] In addition, PVP-2 purchased from Aldrich and PVP-3 purchased from Ashland were prepared as dispersants not containing sulfur element (S).

[0135] The attenuated total reflection (ATR) method was used to confirm whether the first dispersant contained sulfur. In the case of PVP-1, the sulfur content of the first dispersant was 0.1477 W / cm2 at 1030 cm -1 、1160cm -1 / 1200cm -1 The peak was confirmed at Figure 2 ), while PVP-2( Figure 3 ) and PVP-3( Figure 4 ) No peak was confirmed at this position. From the above results, it was confirmed that the first dispersant of PVP-1 was substituted with sulfur.

[0136] <Preparation of Second Dispersant>

[0137] Tannic acid (TA) from Aldrich and polyacrylic acid (PAA, weight average molecular weight: 2000) from Thermo Scientific were prepared.

[0138] <Preparation of Dispersion Liquid>

[0139] Example 1

[0140] 0.4 wt % of CNT-1 as carbon nanotubes, 0.48 wt % of PVP-1 as a first dispersant, 0.12 wt % of TA as a second dispersant, and 99 wt % of distilled water as a solvent were mixed and treated with a high-pressure homogenizer to prepare a carbon nanotube dispersion.

[0141] Examples and Comparative Examples

[0142] For the remaining embodiments and comparative examples, dispersions were prepared by changing the weight and type of each substance as shown in Table 1 below, and their physical properties were tested.

[0143] The compositions of the dispersions prepared in the above examples and comparative examples and the results of each experimental example are shown in the following Table 1. The content of each component is based on the total weight of the dispersion.

[0144] Experimental Example 1: Confirmation of dispersant aggregation

[0145] A test solution was prepared in the same manner as in the above examples and comparative examples except that no carbon nanotubes were added. The test solution was mixed with a vortex mixer at room temperature and allowed to stand for 6 hours, and then coagulation and precipitation were observed.

[0146] It was confirmed that the test solutions of Example 4 and Example 1 did not show agglomeration and precipitation, but the test solution of Comparative Example 1 showed agglomeration and even precipitation of the dispersants ( Figure 1 ).

[0147] Experimental Example 2: Viscosity Measurement

[0148] Using a Brookfield DVNext CP Rheometer, the shear rate was changed to 2.5 sec at 25°C. -1 and 15sec -1 to take measurements.

[0149] Experimental Example 3: Measurement of average particle size

[0150] The laser diffraction method and a commercially available laser diffraction particle size measuring device (Malvern Mastersizer 3000) were used. The average particle size (D50) based on the 50% particle size distribution was calculated by the measuring device. On the other hand, D10 and D90 represent the particle sizes at 10% and 90% particle size distribution, respectively.

[0151] Experimental Example 4: Measurement of sulfur content

[0152] -Sample preparation

[0153] The dispersions prepared in Examples and Comparative Examples were dried in a convection oven at 90° C. for 3 days and then ground using a mixer grinder to prepare powdered samples.

[0154] -Measurement of sulfur content

[0155] The measurement was performed using an elemental analyzer (EA).

[0156] The organic sample is oxidized to CO2, H2O, NO2, and SO2 using a catalyst at high temperature (about 1000°C), and the generated gases are separated using a GC column (Packed column). The TCD (Thermal Conductive Detector) is used for detection, and calibration curves of C, H, N, and S are drawn in advance using standard substances, and the content of each element is quantified in % based on the GC chromatogram.

[0157] Table 1

[0158]

[0159]

[0160] From the above results, it can be confirmed that when the dispersion does not contain sulfur, the viscosity of the dispersion becomes too high (Comparative Examples 1 to 4). This is because the first dispersant and the second dispersant coagulate with each other to increase the viscosity of the dispersion.

[0161] Example 1 includes a first dispersant and a second dispersant that can form hydrogen bonds with each other, but since the first dispersant is substituted with sulfur, the hydrogen bonds between the first dispersant and the second dispersant are suppressed, so that the phenomenon of mutual agglomeration of the dispersants is less likely to occur. In contrast, Comparative Examples 1 and 2 have the same composition as Example 1 except that PVP that is not substituted with sulfur is used as the first dispersant, but since a large number of hydrogen bonds occur between the first dispersant and the second dispersant, there is a problem that the viscosity of the dispersion increases by about 10 times or more.

[0162] Comparative Example 3 has the same composition as Example 5 except that PVP-2 is used as the first dispersant. However, due to a large number of hydrogen bonds between the first dispersant and the second dispersant, the viscosity of the dispersion increases by more than 20 times (@2.5 / s).

[0163] Comparative Example 4 has the same composition as Example 6 except that PVP-2 is used as the first dispersant. However, due to a large number of hydrogen bonds between the first dispersant and the second dispersant, the viscosity of the dispersion increases by more than 20 times (@2.5 / s).

[0164] The methods of adding sulfur to the dispersion include the method of using sulfur-substituted PVP (Examples 1 to 6) and the method of adding sulfide salt (Example 7), and both methods can significantly reduce the viscosity of the dispersion. Among them, it was confirmed that the method of using sulfur-substituted PVP can reduce the viscosity more significantly.

[0165] From the above results, it was confirmed that when the carbon nanotube dispersion liquid contained sulfur, the viscosity could be significantly reduced.

Claims

1. A carbon nanotube dispersion, characterized in that: Include: Carbon nanotubes; a first dispersant having an amide group; A second dispersant having one or more functional groups selected from the group consisting of a hydroxyl group and a carboxyl group; and Sulfur element.

2. The carbon nanotube dispersion according to claim 1, characterized in that: The content of sulfur element is 0.01 wt % or more and 10 wt % or less based on the solid content.

3. The carbon nanotube dispersion according to claim 1, characterized in that: The content of sulfur element is 0.01% or more and 20% or less based on the total content of oxygen (O) and nitrogen (N) elements based on the solid content.

4. The carbon nanotube dispersion according to claim 1, characterized in that: Part or all of the first dispersant is substituted with sulfur.

5. The carbon nanotube dispersion according to claim 4, characterized in that: The ratio of the first dispersant substituted with sulfur in the first dispersant is 10 mol % to 100 mol %.

6. The carbon nanotube dispersion according to claim 1, characterized in that: The first dispersant comprises a selected from 1110cm -1 Up to 1050cm -1 The first peak, 1140cm -1 Up to 1180cm -1 The second peak at 1180 cm -1 Up to 1220cm -1 More than one peak in the group consisting of a third peak.

7. The carbon nanotube dispersion according to claim 1, characterized in that: The first dispersant is polyvinyl pyrrolidone, polyester amide, polycarboxylic acid amide, polyamidoamine, thioamide, a water-soluble nylon compound or a combination thereof.

8. The carbon nanotube dispersion according to claim 1, characterized in that: The second dispersant includes an aromatic ring.

9. The carbon nanotube dispersion according to claim 1, characterized in that: The first dispersant and the second dispersant are contained in a weight ratio of 1:10 to 10:

1.

10. The carbon nanotube dispersion according to claim 1, characterized in that: The specific surface area (BET) of the carbon nanotubes is 10 m 2 / g to 5000m 2 / g.

11. The carbon nanotube dispersion according to claim 1, characterized in that: The average particle size (D50) of the carbon nanotubes is 0.1 μm to 20 μm.

12. A method for preparing a carbon nanotube dispersion according to any one of claims 1 to 11, characterized in that: The method comprises the steps of mixing carbon nanotubes, a first dispersant having an amide group, and a second dispersant having one or more functional groups selected from the group consisting of a hydroxyl group and a carboxyl group.

13. An electrode slurry composition, characterized in that: The method comprises the carbon nanotube dispersion according to any one of claims 1 to 11, an electrode active material and a binder.

14. An electrode, characterized in that: The invention comprises an electrode active material layer formed from the electrode slurry composition according to claim 13.

15. The electrode according to claim 14, characterized in that The above electrode is a negative electrode.

16. A secondary battery, characterized in that: Comprising the electrode according to claim 14.

Citation Information

Patent Citations

  • Device for polishing the surface of the accessory string

    KR1020110118460A

  • Angle aiming mechanism for approach light

    KR1020220112212A

  • Carbon nanotube dispersion liquid, conductor film and conductive film

    CN106414320A

  • Carbon nanotube dispersion and preparation method therefor

    CN112004776A

  • Carbon nanotube dispersion and usage therefor

    CN112424117A